Seeing Gender in Migration: An Introduction - Bludau, Heidi; Ezzeddine, Petra (Lidé města, 2013)
It is well known that, for a long time, gender was absent from studies of migration. Migrants were men and any mention of women or cgildren was in the context of trailing spouses and and other dependents or unskilled and often exploited and/or sexual workers. In general, women were, and to much extent still are, absent from economic data since much of women´s labour is done within the domestic sphere and is not perceived as economic activity. Even when this labour is done outside of the woman´s own home it is invisible to public view. It was only recently that women even entered the public migration narrative. When the "feminization of migration" coincided with feminist and post-modernist movements in social sciences, including anthropology, gender became a primary subject of migration studies.